Synergistic effects of methyl jasmonate treatment and propagation method on Norway spruce resistance against a bark-feeding insect - Berggren, Kristina; Nordkvist, Michelle; Björkman, Christer; Bylund, Helena; Klapwijk, Maartje J.; Puentes, Adriana (Frontiers in Plant Science, 2023)
Utilizing plants with enhanced resistance traits is gaining interest in plant protection. Two strategies are especially promising for increasing resistance against a forest insect pest, the pine weevil (Hylobius abietis): exogenous application of the plant defense hormone methyl jasmonate (MeJA), and production of plants through the clonal propagation method somatic embryogenesis (SE). Here, we quantified and compared the separate and combined effects of SE and MeJA on Norway spruce resistance to pine weevil damage. Plants produced via SE (emblings) and nursery seedlings (containerized and bare-root), were treated (or not) with MeJA and exposed to pine weevils in the field (followed for 3 years) and in the lab (with a non-choice experiment). Firstly, we found that SE and MeJA independently decreased pine weevil damage to Norway spruce plants in the field by 32-33% and 53-59%, respectively, compared to untreated containerized and bare-root seedlings. Secondly, SE and MeJA together reduced damage to an even greater extent, with treated emblings receiving 86-87% less damage when compared to either untreated containerized or bare-root seedlings in the field, and by 48% in the lab. Moreover, MeJA-treated emblings experienced 98% lower mortality than untreated containerized seedlings, and this high level of survival was similar to that experienced by treated bare-root seedlings. These positive effects on survival remained for MeJA-treated emblings across the 3-year experimental period. We conclude that SE and MeJA have the potential to work synergistically to improve plants’ ability to resist damage, and can thus confer a strong plant protection advantage. The mechanisms underlying these responses merit further examination.